Chemical Composition, Total Phenolic Content, and Antioxidant Activities of the Essential Oils of the Leaves and Fruit Pulp of Annona muricata L. (Soursop) from Ghana - Joseph Nana Gyesi; Rita Opoku; Lawrence Sheringham Borquaye (Biochemistry Research International)
Annona muricata, also called soursop, is widespread in many tropical countries, and various parts of the plant have been shown to possess very good pharmacological properties. This work evaluated the chemical composition and antioxidant activities of essential oils obtained from the fruit pulp and leaves of soursop. Essential oils were obtained via hydrodistillation and characterized by gas chromatography-mass spectrometry. Antioxidant potential was evaluated via the phosphomolybdenum, hydrogen peroxide scavenging, and 1,1-diphenyl-2-picrylhydrazyl (DPPH) free radical scavenging assays. In the leaf essential oil, a total of 31 compounds were identified with δ-cadinene (22.58%) and α-muurolene (10.64%) being the most abundant. Thirty-two compounds were identified in the fruit pulp essential oil with Ç-sitosterol (19.82%) and 2-hydroxy-1-(hydroxymethyl) ethyl ester (13.48%) being present in high amounts. Both essential oils showed very good total antioxidant capacities (49.03 gAAE/100 g and 50.88 gAAE/100 g for fruit pulp and leaf essential oils, respectively). The IC50 values from the DPPH assay were 244.8 ± 3.2 μg/mL for leaf essential oil and 512 ± 5.1 μg/mL for the fruit pulp essential oil. At 1 mg/mL, hydrogen peroxide scavenged was below 50% for both leaf and fruit pulp essential oils, indicating moderate activity. These results suggest possible application of the essential oils of Annona muricata in food preservation and processing.